Bisphenols and phthalates: Plastic chemical exposures can contribute to adverse cardiovascular health outcomes - Ramadan, Manelle (Birth Defects Res, 2020)
Phthalates and bisphenols are high production volume chemicals that are used in the manufacturing of consumer and medical products. Given the ubiquity of bisphenol and phthalate chemicals in the environment, biomonitoring studies routinely detect these chemicals in 75–90% of the general population. Accumulating evidence suggests that such chemical exposures may influence human health outcomes, including cardiovascular health. These associations are particularly worrisome for sensitive populations, including fetal, infant and pediatric groups—with underdeveloped metabolic capabilities and developing organ systems. In the presented article, we aimed to review the literature on environmental and clinical exposures to bisphenols and phthalates, highlight experimental work that suggests that these chemicals may exert a negative influence on cardiovascular health, and emphasize areas of concern that relate to vulnerable pediatric groups. Gaps in our current knowledge are also discussed, so that future endeavors may resolve the relationship between chemical exposures and the impact on pediatric cardiovascular physiology.